ANALISIS KEPATUHAN FINANSIAL DAN NON FINANSIAL PPH PASAL 23 DAN PASAL 25 - Yustinus Khristiandri; Susi Dwimulyani (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2017)
This research aims to analyze the tax financial compliance calculating, payment, and reporting tax obligations and nonfinancial compliance in Accuracy of depositing and reporting date Income tax obligations of Article 23 and 25 has been done in 2015 in accordance with applicable tax laws in 2015. Methods of data collection in this research include interviews, observations, documentation from PT XYZ for further analysis. Data analysis are performed by comparing the calculation, payment, reporting of tax obligations (tax payment slip and tax return). Fiscal corrections has been done by PT XYZ under 2015 tax regulations. Results revealed that the tax obligations of financial XYZ is in the calculation and remittance of income tax Article 23, including taxpayers who do not obey, because there is still an object of Income Tax Article 23, namely the cost of consultancy services, uncut, fully paid and reported. Compliance nonfinancial XYZ in the reporting obligations of Income Tax Article 23 is still not comply because there is still an object of income tax Article 23 on consultancy services, uncut , filly paid and reported in August and Income Tax Article 25 XYZ 2015 are in accordance with prevailing tax regulations. Namely the obligation of article 25 PT XYZ has been deposited before the maturity deposit and reporting of income tax Article 23 for further research can be developed into more comprehensive tax liability.